Morphology and Starch Production Potential of Sago Palm Found in Village Haripau, East Mimika Subdistrict, Mimika, Papua Province, Indonesia - Nurulhaq, Muhammad Iqbal; Bintoro, Muhammad Hasjim; Supijatno, Supijatno (Journal of Tropical Crop Science, 2022)
Papua, Indonesia is the largest sago palm (Metroxylon spp) distribution area in the world. Most (85%) of the total sago area in the world is in Indonesia, and 95% of the sago area in Indonesia is in Papua and West Papua. Field observation of accessions of sago palm was conducted at the sago growing area at Hiripau village. The aim of the study was to determine the diversity of sago palm accessions from Hiripau village and compare their morphology and starch production. Based on interviews with the local farmers, the four accessions of sago palm that dominated the Hiripau area are Nakowai, Mapartaro, Tuhai, and Korearipi. These accessions vary in the spine characteristics, features of the trunk, leaf, pith, and starch production. Sago Mapartaro leaves are the largest (23.56 m2) and the leaflet areas are almost twice the size of the other accessions. Tuhai has the highest starch yield but it has high ash content resulting in low starch quality.